Analisis Geometri Jalan Tambang Batubara Pada Kegiatan Overburden Removal di PT Satria Alam Manunggal Site TOP Desa Buhut Jaya Kabupaten Kapuas Provinsi Kalimantan Tengah: Analysis Of Mine Road Geometry In Overburden Removal Activities At PT Satria Alam Manunggal Site TOP Buhut Jaya Village Kapuas Regency Central Kalimantan Province - Anisa Anisa; Deddy Nan Setya Putra Tanggara; Dody Ariyantho Kusma Wijaya; Noveriady Noveriady; Asri Fridtriyanda (Media Ilmiah Teknik Sipil, 2026)
This study was conducted at PT Satria Alam Manunggal Site TOP to analyze the effect of road geometry conditions on the performance of Scania P410-B6x4 transport equipment in overburden material transportation activities. The haul route from the front to the disposal site is 2.4 km long, with an average hauler productivity of 33 BCM/hour, while the company's target is set at 40 BCM/hour. This situation indicates an issue with the hauler's travel time when transporting overburden material from the front to the disposal site, resulting in the hauler's productivity not being achieved. The analysis was conducted by dividing the haul road into 29 segments, consisting of 27 straight segments and 7 curved segments. The minimum width of straight roads is 9.1 meters for two lanes and 5.2 meters for one lane, while for curves, the minimum width is 16.29 meters and 9.31 meters, with a maximum road gradient (grade) of 8%, as well as other elements such as curve radius, superelevation, cross slope, safety berm, and drainage channels, also affect operational comfort and safety. The objective of this study is to evaluate and provide recommendations for road geometry improvements to meet technical standards, thereby reducing travel time and increasing transportation vehicle productivity.